Expression and characterization of an ice binding protein from a bacterium isolated at a depth of 3,519 meters in the Vostok ice core, Antarctica - Achberger, Amanda M.; Brox, Timothy I.; Skidmore, Mark L.; Christner, Brent C. (Frontiers in Microbiology, 2011)
Cryopreservation of microorganisms in ancient glacial ice is possible if lethal levels of macromolecular damage are not incurred and cellular integrity is not compromised via intracellular ice formation or recrystallization. Previously, a bacterium (isolate 3519-10) recovered from a depth of 3,519 meters below the surface in the Vostok ice core was shown to secrete an IBP that inhibits the recrystallization of ice. To explore the advantage that IBPs confer to ice-entrapped cells, experiments were designed to examine the expression of 3519-10’s IBP gene and protein at different temperatures, assess the effect of the IBP on bacterial viability in ice, and determine how the IBP influences the physical structure of the ice. Total RNA isolated from cultures grown between 4 to 25⁰C and analyzed by reverse transcription-PCR indicated constitutive expression of the IBP gene. SDS-PAGE analysis of 3519-10’s extracellular proteins also revealed a polypeptide of the predicted size of the 54 kDa IBP at all temperatures tested. In the presence of 100 µg mL-1 of extracellular protein from 3519-10, the survival of Escherichia coli was increased by greater than 34-fold after freeze-thaw cycling. Microscopic analysis of ice formed in the presence of the IBP indicated that per mm2 field of view, there were ~5 times as many crystals as in ice formed in the presence of washed 3519-10 cells and non-IBP producing bacteria, and ~10 times as many crystals as in filtered deionized water. Presumably, the effect that the IBP has on bacterial viability and ice crystal structure is due to its activity as an inhibitor of ice recrystallization. A myriad of molecular adaptations are likely to play a role in bacterial persistence under frozen conditions, but the ability of 3519-10’s IBP to control ice crystal structure, and thus the liquid vein network within the ice, may provide one explanation for its successful survival deep within the Antarctic ice sheet for thousands of years.